Homegrown: identity and difference in the American war on terror - Szpunar, Piotr M. (Critical cultural communication, 2018)
Entrance: a theory of the double -- Defining terror : through identity and in time -- Informants and other media : networking the double -- Opacity and transparency in counterterrorism : belonging and citizenship post-9/11 -- No exit -- Epilogue -- Acknowledgments -- Notes -- Bibliography -- Index -- About the author